Current practices of canal wall up versus canal wall down mastoidectomy: a review - Swain, Santosh K. (International Journal of Research in Medical Sciences, 2024)
To achieve a disease-free and dry ear is the goal of mastoidectomy in chronic otitis media (COM) with or without cholesteatoma. The operating surgeon, the patient, and the disease process all have a role in the surgical procedure selection. In the case of cholesteatoma with COM, the surgeon has significant hurdles in the prevention of recurrent disease and the maintenance of hearing. Canal wall up (CWU) and canal wall down (CWD) are the surgical methods used for treatment of the COM with cholesteatoma. The importance of surgical method outcomes has been highlighted in recent surgical works, not only in terms of technical success but also in connection to the impact of therapy on patients' quality of life and welfare. The surgical procedures of CWP and CWD usually alter the middle ear structures which affect the transmission of sound from the tympanic membrane to the cochlea. The kind of disease, the depth of the pathology, and the patient's overall condition all have a role in the decision to use a surgical technique like CWU or CWD in COM. Due to improved audiometric results and simpler postoperative care, the CWU approach is frequently preferred despite having a greater probability of revision surgery. CWD surgical techniques usually lower the residual/recurrent rates of cholesteatoma. With regard to the surgical management of COM with cholesteatoma, this review article compares the effectiveness and current procedures of CWU mastoidectomy and CWD mastoidectomy.